SYNTHESIS OF 3-ALKYLIDENECEPHAM-4-CARBOXYLIC ACID-DERIVATIVES BY SAMARIUM(II) IODIDE REDUCTION - KANG, HY; CHO, YS; KOH, HY; CHANG, MH (MARCEL DEKKER INC, 1993)
Samarium(II) iodide promoted reductive deacetoxylation of 7-aminocephalosporanic acid derivatives to synthesize 3-alkylidenecepham-4-carboxylates, which could be valuable intermediates for the synthesis of new cephalosporin antibiotics, was investigated.
Keywords: ORGANIC-SYNTHESIS; EFFICIENT ROUTE; LANTHANIDES; DIIODIDE; ESTERS